Educación financiera y nivel de endeudamiento en la ciudad de Riobamba periodo 2019 - Valeria Maitte, Yambay Ordoñez (2020)
Financial inclusion together with financial education are important tools to promote social equality and economic growth through proper financial stability, the objective of this research is to determine the main factors that occur in financial education and how they affect the level of indebtedness in the Riobamba city, period 2019. By conducting surveys and multinomial logistic regression, it is empirically proven that, if there is a relationship between the variables, and that there is a high probability that people will be in excessive debt. The research comprises four sections, in the first one, the reference framework is developed in which the introduction, the problem approach and the formulation of objectives are explained, in the second part the methodological framework is detailed in which the main definitions are explained, about financial education and indebtedness. The third section, which presents the research methodology, the econometric model applied and the analysis and discussion of results, and in the last part, the conclusions and recommendations are appreciated.